The potential role of UV and blue light from the sun, artificial lighting, and electronic devices in melanogenesis and oxidative stress. - Navarrete-de-Gálvez, Enrique; Aguilera-Arjona, José; Solis Almellones, Alba; De-Gálvez-Aranda, María Victoria; Andrés-Díaz, José Ramón; Herrera-Ceballos, Enrique; Gago-Calderón, Alfonso (Elsevier, 2022)
Our exposure to blue light from artificial sources such as indoor lights (mainly light-emitting diodes [LEDs]) and electronic devices (e.g., smartphones, computer monitors, and television screens), has increased in recent years, particularly during the recent coronavirus disease 2019 lockdown. This radiation has been associated to skin damage across its potential in generating reactive oxygen species in both the epidermis and the dermis, skin water imbalances and of potential activating melanin production. These circumstances make it important to determine whether current blue light exposure levels under artificial illumination and electronic devices expo- sure can cause the previously indicated disorders as compared to solar UV and visible radiation in a typical summer day. Blue light accounted for 25% of the sun’s rays, approximately 30% of radiation emitted by elec- tronic devices, and approximately from 6% to 40% of that emitted by indoor lights. The reference equations showed that the sun was the main source of effective irradiance for immediate and persistent pigmentation as well as for potential oxidative stress in our skin. Effective blue light exposure to artificial devices is significantly lower than the solar contribution. However, its contribution must be considered as accumulative dose effect, and especially in people with hypersensitivity promoting skin hyperpigmentation.
Keywords: Pigmentación; Piel - Efectos de la radiación; Estrés oxidativo; Action spectrum; Blue light; Oxidative stress; Skin hyperpigmentation; LED technology; Solar radiation